Managing oneself : and What makes an effective executive - Drucker, Peter F. 1909-2005, (Harvard Business Review Press, 2017)
Peter Drucker is widely regarded as the father of modern management, offering penetrating insights into business that still resonate today. But Drucker also offers deep wisdom on how to manage our personal lives and how to become more effective leaders. In these two classic articles from "Harvard Business Review," Drucker reveals the keys to becoming your own chief executive officer as well as a better leader of others. "Managing Oneself" identifies the probing questions you need to ask to gain the insights essential for taking charge of your career, while "What Makes an Effective Executive" outlines the key behaviors you must adopt in order to lead. Together, they chart a powerful course to help you carve out your place in the world. -- Provided by publisher.